Using a classroom response system to support active learning in an educational psychology course: A case study. - Artino, Anthony R.; Ioannou, Andri (My University, 2010)
This study examined undergraduates' attitudes toward the use of a classroom response system (CRS) in an educational psychology course. We employed a CRS in an effort to enhance interactivity, maintain student interest, and provide real-time, formative feedback. Approximately 10 weeks after introduction, students' attitudes toward the technology were assessed using quantitative and qualitative data sources. In general, the CRS was well received by students and appeared to serve its intended purposes. In particular, students positively endorsed our instructional use of the technology and felt it was an innovative method for checking their understanding of course material; enhancing classroom interactivity; maintaining student interest, engagement, and concentration; and making lectures more enjoyable. Educational implications and future directions are discussed
Keywords: Case studies; Experiential learning; Student response systems